OBSTACLES AND OPPORTUNITIES FOR VOCATIONAL EDUCATION IN QUEBEC - Hodder, Janyne M. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1994)
The importance of vocational education on both the individual level (satisfaction, employment, and quality of life) and the societal level (productivity and economic growth) is reviewed, and the advocacy of vocational education programs by the ministère de l’Éducation du Québec is explained in the context of concern for the future of children and young people in Quebec. It is argued tkat school counsellors may no longer rely on outdated biases against vocational education, and should encourage students to make their own wise academic and career choices. RÉSUMÉ L’auteur analyse l’importance de la formation professionnelle au niveau individuel (satisfaction, emploi et qualité de vie) et au niveau sociétal (productivité et croissance économique) tandis qu’elle explique la défense des programmes de la formation professionnelle par le ministère de l’Éducation du Québec par rapport aux préoccupations soulevées par l’avenir des enfants et des jeunes du Québec. L’auteur soutient que les conseillers scolaires doivent se débarrasser de leurs préjugés à l’égard de la formation professionnelle et inciter leurs étudiants à opérer leurs propres choix de carrière.